(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
This study aims to examine the effect of float stitches on the key comfort properties of rib-knitted fabrics. Knit pattern, as a structural parameter, plays a significant role in determining fabric behaviour, and this research evaluates how variations in float stitches affect air permeability, water vapour permeability, thermal resistance, and related comfort characteristics. The findings show that incorporating float stitches reduces both air and water vapour permeability, while increasing thermal resistance, thereby making these fabrics more suitable for winter clothing due to enhanced thermal insulation. An increase in the number of float stitches across successive courses further raises water vapour permeability, thermal resistance, and energy absorption, but lowers air permeability and resiliency. When float stitches are present on both sides of the fabric, thermal resistance, energy absorption, resilience, and thickness recovery improve, whereas air permeability, water vapour permeability, and relative compressibility decrease compared to fabrics with floats on only one side. The study indicates that fabrics with float stitches on one side are better suited for summer clothing due to their improved moisture management, while those with float stitches on both sides are more suitable for winter use, owing to their superior thermal insulation.